Hubungan Antara Persepsi Siswa Dengan Hasil Belajar Dalam Pembelajaran Seni Budaya Di SMP Negeri 4 Padang - Sari Puspa Utami; Afifah Asriati; Susmiarti Susmiarti (SENDRATASIK UNP, 2019)
The article aimed to know and describe the relationship between students’ perception toward the results of the study of art and culture in SMP Negeri 4 Padang. Type of the research was used in this research was quantitative with the correlational method (relationship). Correlational research intended to examine whether there was a relationship between students’ perception toward the results of the study of art and culture in grade IX SMP Negeri 4 Padang or not. The population in this research was all of students in grade IX of SMP Negeri 4 Padang which was 204 of students meanwhile the research sample was 67 of students from the whole grade IX which was taken by using Slovin formula. The instruments were used to obtain data were questionnaires and report of students’ results in the odd semester (1) in 2018/2019. Results of the research showed that there was a relationship between students’ perceptions toward the results of the study. The correlation of test results with the values was obtained for the variable X (students’ perception) and the variable Y (result of the study) was 0.7954 while rtable was rcount, so 0.2404 > rtable. Then it can be drawn the conclusion that the relationship is positive and significant and it can be proceeded by using significance test. Significance test is sought by using t test so that the variable results obtained is tcount = 10,579 and ttable = 1,996 (tcount > ttable) to X (the student's’ perception) toward Y (the result of study). Then it can be drawn the conclusion that Ha is accepted.